THE ROLE OF POVERTY ALLEVIATION IN BOJONEGORO: FLOOD WELL-MAINTAIN - Sri Suryaningsum; Moch Irhas Effendi; Hendri Gusaptono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2015)
This paper discusses about flood that usually happens in some regions in Indonesia especiallyin the rain season. Flood is one of scary phenomenon for people who are not well-prepared toface it. It is believed as natural disaster because it comes from the overflow of river.However, it also happens because of human activities who unconsciously often throw rubbishinto the river, that makes the water cannot well-flown, stagnant, and the water will overflow.Another cause is illegal logging in the forest, that decrease the absorption area of rain waterand causes flood.The flood that will be discussed in this writing is flood that happens in Bojonegoro. Thepeople there are well-prepared to face it, especially at about these last 6 years. And the onewho responsible for it is Suyoto as the district leader (Bupati) of Bojonegoro. Suyoto isclaimed to be successful man to lead and prepare Bojonegoro people to face flood. He hascertain treatments to make flood not as a scary phenomenon for them. Flood is one of thegifts of God for Bojonegoro people that can help their life.The conclusion of this paper is that the good maintenance of flood in Bojonegoro maybecome the role model for other regions. The stakeholders of government and the citizens areunited as one team, together in facing flood.Keywords: Flood, good maintenance of flood